2021
DOI: 10.1111/tri.13975
|View full text |Cite
|
Sign up to set email alerts
|

A meta‐analysis on the incidence of donor‐related depression after liver transplant

Abstract: Summary Living donor liver transplantation (LDLT) is increasing, yet gaps exist in the understanding of psychological wellbeing of donors after liver transplant. This meta‐analysis seeks to evaluate the incidence and risk factors for donor‐related depression after liver transplantation. A search was conducted on Medline and Embase database. Articles assessing incidence of depression in LDLT donors were included. Incidence was pooled after Freeman–Turkey double‐arcsine transformation. For risk factors, dichotom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 78 publications
0
6
0
Order By: Relevance
“…This is particularly concerning as the incidence of psychological complications is likely to be underestimated owing to the cultural stigma associated with mental health in the Asian context. [27,28] Moreover, previous studies have estimated the prevalence of suicide and suicide attempts among living liver donors at 0.25%. [29][30][31] Notably, only 2 studies in this meta-analysis reported data regarding suicide among living liver donors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is particularly concerning as the incidence of psychological complications is likely to be underestimated owing to the cultural stigma associated with mental health in the Asian context. [27,28] Moreover, previous studies have estimated the prevalence of suicide and suicide attempts among living liver donors at 0.25%. [29][30][31] Notably, only 2 studies in this meta-analysis reported data regarding suicide among living liver donors.…”
Section: Discussionmentioning
confidence: 99%
“…To date, several risk factors have been identified as potential predictors of poorer psychosocial outcomes in liver donors, including female sex, recipient death, employment status, and lower education levels. [34,35] The eligibility of donors at risk of psychological issues post-liver donation should be reconsidered to protect these vulnerable individuals and potentially reduce the incidence of post-organ donation suicide rate. Beyond pre-donation assessment and counselling, the establishment of a lifelong follow-up program with regular psychiatric evaluations using validated tools and the provision of dedicated psychosocial support services are vital to mitigate the risk of psychological complications and its repercussions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depression was significantly higher in Asian compared with western populations (RR: 1.73, CI 1.19-2.52, P ¼ 0.0039), while being female, Caucasian, unemployed and with lower education level were factors associated with depression. The level of depression was not influenced by the relationship with the recipient [65]. A metanalysis of 15 articles reporting on mental status of kidney donors found that depression decreased after transplantation [66].…”
Section: Depression In Living Organ Donorsmentioning
confidence: 96%
“…As mentioned above, with the increase in depression exploration, extracerebral pathological alterations have been paid more and more attention. As the main organ of lipid metabolism, especially the metabolism of epoxide, the liver has been proposed to have an unexpected connection with brain functions [ 101 , 102 , 103 , 104 , 105 ]. The pathogenesis of Alzheimer’s disease (AD) is believed to be closely related to depression [ 106 , 107 ].…”
Section: Depression-associated Seh Promotes Liver Dysfunction and Bre...mentioning
confidence: 99%